Insulin Resistance Is a Risk Factor for Overall Cerebral Small Vessel Disease Burden in Old Nondiabetic Healthy Adult Population - Yang, Xiaoli; Zhang, Shufan; Dong, Zhiyuan; Zi, Yincui; Luo, Yufan; Jin, Zhi; Shi, Lei; Li, Chen; Ren, Chuanchen; Wu, Danhong (Frontiers in Aging Neuroscience, 2019)
Background and Purpose: This study aimed to investigate the association between insulin resistance (IR) and the overall cerebral small vessel disease (CSVD) burden. Methods: We recruited elderly, nondiabetic, healthy subjects prospectively. The overall effect of CSVD on the brain was described by a validated CSVD score. The homeostasis model assessment–estimated insulin resistance index (HOMA-IR) was used for IR estimation, and HOMA-IR ≥2.80 was defined as IR. We evaluated the association between IR and the increasing severity of CSVD score by ordinal regression models adjusting for demographics and cardiovascular risk factors. Results: A total of 156 healthy participants were recruited. The mean age was older in the IR group than in the non-IR group (70.03 vs. 67.45, p = 0.04), and the prevalence of hypertension was significantly higher in the IR group than in the non-IR group (82.35% vs. 53.28%, p < 0.01). In ordinal regression analysis, IR was positively associated with increasing severity of the total CSVD score (adjusted odds ratio, 3.74; 95% confidence interval, 1.63–5.08; p < 0.01) after adjusting traditional risk factors. Furthermore, HOMA-IR levels showed a positive dose-dependent correlation with the total CSVD score (p < 0.01, p for trend <0.01). Conclusions: IR is independently associated with increasing severity of the overall CSVD burden, independent of other clinical risk factors in an elderly, nondiabetic, healthy population. Furthermore, HOMA-IR level is correlated with the CSVD burden in a dose-dependent manner.